2015
DOI: 10.1002/ajmg.c.31458
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and prevention of child abuse in the child with disability

Abstract: Children with disabilities (CWD) are victims of abuse more frequently than children in the general population. The features of their underlying conditions make it more difficult to detect abuse and on occasion can be mistaken for abuse. Thus, the expertise of the clinical geneticist is often vital to properly identifying maltreatment in this vulnerable population. The purpose of this article is to review the magnitude of abuse in the population of CWD, to identify the aggravating factors, and to suggest practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 46 publications
0
13
0
3
Order By: Relevance
“… 18 , 19 Additionally, many reports stated that MS paradigms cause long-lasting changes in anxiety-like, depression-like, and social behaviors in mice. 20 22 Although a recent report found that children with disabilities are more frequently victims of abuse than healthy children, 23 the effects of early-life adversity on pups with atypical neurodevelopment are poorly understood. In this study, we applied an MS paradigm to motopsin KO mice to examine its effects on adulthood behaviors.…”
Section: Introductionmentioning
confidence: 99%
“… 18 , 19 Additionally, many reports stated that MS paradigms cause long-lasting changes in anxiety-like, depression-like, and social behaviors in mice. 20 22 Although a recent report found that children with disabilities are more frequently victims of abuse than healthy children, 23 the effects of early-life adversity on pups with atypical neurodevelopment are poorly understood. In this study, we applied an MS paradigm to motopsin KO mice to examine its effects on adulthood behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…; Wills et al . ), because the physical and emotional signals of abuse are often mistakenly attributed to their disability (Nowak ). Ongoing child abuse has potentially disastrous consequences (Reijneveld et al .…”
Section: Discussionmentioning
confidence: 99%
“…This might be related to the relatively high incidences of parental abuse and internalising problems in this profile. It is established that recognition of abuse is particularly difficult in persons with ID (Reijneveld et al 2008;Wills et al 2008), because the physical and emotional signals of abuse are often mistakenly attributed to their disability (Nowak 2015). Ongoing child abuse has potentially disastrous consequences (Reijneveld et al 2008), including the development of internalising disorders, which were prevalent in profile 3.…”
Section: Discussionmentioning
confidence: 99%
“…Sowohl in Europa als auch in den USA ist von einer Inzidenz von ca. 25-30/100.000 für misshandlungsbedingte ZNS-Verletzungen im Säuglingsalter auszugehen [16,17]. Die Daten der Erhebungseinheit für seltene pädiatrische Erkrankungen in Deutschland (ESPED) ergeben 17,6/100.000 bis zu einem Alter von einem Jahr, dies entspricht jährlich ca.…”
Section: Epidemiologieunclassified